Does ESG Performance Accelerate SDG Convergence? Evidence from Indonesia and Emerging Markets, 2000–2022 - Nelyumna Rizal; Eka Sudarmaji (Greenation Research & Yayasan Global Resarch National, 2026)
This study investigates whether Environmental, Social, and Governance (ESG) performance functions as a structural catalyst for Sustainable Development Goal (SDG) convergence toward OECD benchmarks among emerging market economies. Positioned at the intersection of international development economics and corporate sustainability research, the paper addresses a clear empirical gap: while prior literature has documented rising ESG disclosure and improving SDG scores in developing nations independently, the conditional relationship between ESG pillar quality and the speed of SDG catching up remains unexamined at the country level, particularly in Southeast Asia. Using the Sustainable Development Report 2023 (N = 166 countries) and the SDG Index 2000–2022 panel dataset (4,140 observations), this study applies a four-stage methodological framework comprising Kruskal-Wallis non-parametric group tests, beta-convergence regression, Spearman rank correlation analysis, and an ESG-SDG gap decomposition aligned with the three-pillar ESG taxonomy. Results reveal significant unconditional beta-convergence in global SDG performance (β = −0.0042, p < .001), confirming that lower-scoring countries improve faster. Indonesia presents a compelling case: it records the strongest SDG 9 improvement trajectory in ASEAN (slope = +3.807 points per year, R² = 0.872 post-2015) yet remains 35.0 points below the OECD average on industry and innovation—its largest governance-pillar gap. Spearman correlations identify SDGs 3, 1, 9, and 16 as the most structurally embedded goals in overall national SDG performance (ρ > 0.84). The analysis maps each critical gap onto the corresponding ESG pillar, showing that Governance-aligned SDGs carry the deepest absolute deficits. These findings suggest that targeted governance ESG improvements—in supply chain accountability, board transparency, and institutional R&D investment—represent the highest-leverage pathway for Indonesia and comparable emerging economies to accelerate SDG convergence. Policy implications center on OJK regulatory enhancement and Bappenas-aligned ESG-SDG co-investment frameworks.